Analysis of the transcriptomes downstream of Eyeless and the Hedgehog, Decapentaplegic and Notch signaling pathways in Drosophila melanogaster. - Landry E Nfonsam (Public Library of Science (PLoS), 2012)
Tissue-specific transcription factors are thought to cooperate with signaling pathways to promote patterned tissue specification, in part by co-regulating transcription. The Drosophila melanogaster Pax6 homolog Eyeless forms a complex, incompletely understood regulatory network with the Hedgehog, Decapentaplegic and Notch signaling pathways to control eye-specific gene expression. We report a combinatorial approach, including mRNAseq and microarray analyses, to identify targets co-regulated by Eyeless and Hedgehog, Decapentaplegic or Notch. Multiple analyses suggest that the transcriptomes resulting from co-misexpression of Eyeless+signaling factors provide a more complete picture of eye development compared to previous efforts involving Eyeless alone: (1) Principal components analysis and two-way hierarchical clustering revealed that the Eyeless+signaling factor transcriptomes are closer to the eye control transcriptome than when Eyeless is misexpressed alone; (2) more genes are upregulated at least three-fold in response to Eyeless+signaling factors compared to Eyeless alone; (3) based on gene ontology analysis, the genes upregulated in response to Eyeless+signaling factors had a greater diversity of functions compared to Eyeless alone. Through a secondary screen that utilized RNA interference, we show that the predicted gene CG4721 has a role in eye development. CG4721 encodes a neprilysin family metalloprotease that is highly up-regulated in response to Eyeless+Notch, confirming the validity of our approach. Given the similarity between D. melanogaster and vertebrate eye development, the large number of novel genes identified as potential targets of Ey+signaling factors will provide novel insights to our understanding of eye development in D. melanogaster and humans.